Accumulation of Major Histocompatibility Complex Class II Molecules in Mast Cell Secretory Granules and Their Release upon Degranulation - Raposo, Graça (The American Society for Cell Biology, 1997)
To investigate the relationship between major histocompatibility complex (MHC) class II compartments, secretory granules, and secretory lysosomes, we analyzed the localization and fate of MHC class II molecules in mast cells. In bone marrow-derived mast cells, the bulk of MHC class II molecules is contained in two distinct compartments, with features of both lysosomal compartments and secretory granules defined by their protein content and their accessibility to endocytic tracers. Type I granules display internal membrane vesicles and are accessed by exogenous molecules after a time lag of 20 min; type II granules are reached by the endocytic tracer later and possess a serotonin-rich electron-dense core surrounded by a multivesicular domain. In these type I and type II granules, MHC class II molecules, mannose-6-phosphate receptors and lysosomal membrane proteins (lamp1 and lamp2) localize to small intralumenal vesicles. These 60–80-nm vesicles are released along with inflammatory mediators during mast cell degranulation triggered by IgE-antigen complexes. These observations emphasize the intimate connection between the endocytic and secretory pathways in cells of the hematopoietic lineage which allows regulated secretion of the contents of secretory lysosomes, including membrane proteins associated with small vesicles.